A randomized controlled trial of plastic drape for prevention of hypothermia during umbilical catheterization - Pracha Nuntnarumit (2018)
Objective To determine the efficacy of polyethylene plastic draping in preventing hypothermia during umbilical catheterization. Methods A randomized controlled trial was conducted in newborns who required umbilical catheterization. A sterile polyethylene plastic sheet covering the procedural field was used in the plastic group, and a sterile conventional cotton drape was used in the control group. Results Sixty infants were enrolled and randomly assigned to the plastic group (n = 30) and control group (n = 30). There were no significant differences in the baseline demographic data. The use of plastic drapes was associated with a higher rectal temperature compared with the control group. Incidence of hypothermia at the end of procedure were 20% and 50% in the plastic group and control group, respectively (p = 0.03). Conclusion Polyethylene plastic draping was superior to conventional cloth draping in maintaining rectal temperature and preventing hypothermia during umbilical catheterization. © 2013 by Thieme Medical Publishers, Inc.